Solutions and Procedures for Repairing a Damaged Vertical Cylindrical Tank – Depositor - Doncheva, Elisaveta; Gochev, Viktor; Krstevska, Aleksandra (ELSEVIER B.V., 2023)
This research paper describes and evaluates the options for repairing and rehabilitating a damaged vertical cylindrical tank (depositor). The vertical cylindrical tank is part of a wastewater treatment plant located in the vicinity of a metallurgical plant for the production of ferrosilicon Jugohrom Alzar LTD, and its components, shell, and floor are severely damaged as a result of the tank's long-term exploitation and improper maintenance. The tank is used in a wastewater treatment plant station to reduce and neutralize the carcinogen hexavalent chromium (Cr VI) into Cr-III. Two repair techniques are analyzed and investigated. The first is to repair the damage by restoring the required projected thickness of the sheet metal walls through repair welding. The other method is to apply liquid metals to the damaged areas to achieve the required projected thickness of the materials of the individual components. Mechanical tests are required regardless of which of the two repair methods is used. In order to obtain a more realistic picture of the influence of the weld, respectively of the liquid metal, samples were made according to the tensile test standard, ISO 6892-1, on which damages similar to those found on the tank were done. The obtained experimental results, along with the discussions for future research possibilities, contribute to upgrading and enhancing current knowledge in the direction of finding the most appropriate way to repair the damage that occurs in vertical cylindrical tanks as a result of their long-term exploitation.
Keywords: vertical cylindrical tank; damage; welding; advanced materials